Safety and adherence of pressure garment therapy in children with upper limb unilateral cerebral palsy. Results from a randomized clinical trial ancillary analysis - Béghin, Laurent; Mohammad, Yasser; Fritot, Séverine; Letellier, Guy; Masson, Sixtine; Zagamé, Yann; Donskoff, Catherine; Toussaint-Thorin, Mathide; Gottrand, Laurence (Frontiers in Pediatrics, 2023)
Background : This study was conducted to assess safety and adherence of the use of a PGT (Pressure Garment Therapy) Lycra sleeve to treat upper limb unilateral cerebral palsy (UCP) in children. Methods : This study was conducted as a prospective, placebo-controlled, double-blinded, randomized monocenter study. 58 UCP children were included and 49 were analyzed. 25 children (mean age 6.6 ± 1.6 years ; 12 girls) were allocated to the active group vs 24 (mean age 6.7 ± 1.6 years ; 10 girls in the placebo group). The intervention consisted by an active PGT Lycra arm sleeve manufactured to generate a homogeneous pressure ranging from 15 to 25 mmHg. The placebo PGT Lycra sleeve was manufactured to generate a homogeneous pressure under 7 mmHg. The time of wearing period was set at 3 h/day at minimum and 6 h/day at maximum, during 6 months. The main outcome measures were safety outcomes included the number and intensity of Adverse Events of Special Interest (AESIs). AESIs were defined as adverse event imputable to compressive therapy and Lycra wearing, Level of adherence was expressed in percentage of number of days when sleeve was wear at least 3 hours per day compared to length of duration in days (start and end date of wearing period). Results : Frequency of AESIs were very low and no different between groups (4.12 ± 11.32 vs 1.83 ± 3.38 % ; p=0.504). There were no difference in adherence (91.86 ± 13.86 vs 94.30 ± 9.95 % ; p = 0.425). Conclusion : The use of PGT Lycra® arm sleeve in children with UCP is safe, well-tolerated with a very good adherence. The low rate of AESIs is promising for further randomized clinical trials on efficacy.